2011
DOI: 10.1002/jbmr.403
|View full text |Cite
|
Sign up to set email alerts
|

Effects of denosumab on fracture and bone mineral density by level of kidney function

Abstract: The incidences of osteoporosis and chronic kidney disease (CKD) both increase with increasing age, yet there is a paucity of data on treatments for osteoporosis in the setting of impaired kidney function. We examined the efficacy and safety of denosumab (DMAb) among subjects participating in the Fracture Reduction Evaluation of Denosumab in Osteoporosis Every 6 Months (FREEDOM) Study. We estimated creatinine clearance (eGFR) using Cockcroft-Gault and classified levels of kidney function using the modified Nati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
176
2
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 300 publications
(193 citation statements)
references
References 19 publications
4
176
2
3
Order By: Relevance
“…(21) Our findings are also consistent with what has been reported in post hoc analyses from the registration trials for antiresorptive agents used in the treatment of osteoporosis. (22)(23)(24)(25) Some women in these trials had an eGFR consistent with stage 4 CKD, and some had stage 5 CKD despite a serum creatinine in the normal range. In these post hoc analyses, low BMD was a strong and consistent risk factor for fracture.…”
Section: Discussionmentioning
confidence: 99%
“…(21) Our findings are also consistent with what has been reported in post hoc analyses from the registration trials for antiresorptive agents used in the treatment of osteoporosis. (22)(23)(24)(25) Some women in these trials had an eGFR consistent with stage 4 CKD, and some had stage 5 CKD despite a serum creatinine in the normal range. In these post hoc analyses, low BMD was a strong and consistent risk factor for fracture.…”
Section: Discussionmentioning
confidence: 99%
“…The use of drugs such as bisphosphonates, teriparatide, and denosumab, which have been shown to reduce fracture incidence in patients with normal kidney function, is controversial in patients with CKD. Post hoc analyses of several phase III studies suggest these agents can be administered safely to patients with mild to moderate CKD without biochemical evidence of the mineral and bone disorder and that fracture risk is reduced significantly (23)(24)(25)(26)(27). However, those studies included relatively few subjects with more severe CKD.…”
mentioning
confidence: 99%
“…Next, we address the hypocalcemia induced by DMAb in patients with CKD. Previous studies reported that hypocalcemia was the most common adverse effect of DMAb (Jamal et al 2011;Chen et al 2014). In addition, recent studies showed that treatment with DMAb induced severe hypocalcemia in CKD patients (particularly, CKD stage 4-5D patients complicated with SHPT) compared to the general population (Jamal et al 2010;Dave et al 2015).…”
Section: Discussionmentioning
confidence: 96%
“…Also, in other previously reported cases regarding DMAb therapy for CKD patients, severe hypocalcemia was observed just after administration (Talreja 2012;McCormick et al 2012;Torregrosa 2013;Agarwal et al 2013;Ungprasert et al 2013;Farinola and Kanjanapan 2013;Dusilova Sulkova et al 2014). On the other hand, rapid increase in i-PTH levels is also recognized to be associated with DMAb therapy in patients with CKD (Jamal et al 2011;Chen et al 2014;Dave et al 2015). Of note, Chen et al (2014) showed that a high i-PTH level was an important predictor of severe hypocalcemia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation